An investigation on the determinants of bank failures in Zimbabwe: 2009-2012 - Katuka, Blessing (Midlands State University, 2014)
Upsurge in bank failure cases under a more stable currency environment raised the need to deeply investigate sources of bank failures in Zimbabwe. This is considered an imperative move considering the impact that bank failures pose to stakeholders outside the banking sector such as investors and depositors, the Zimbabwean banking sector itself as well as the entire economy. This study investigated the determinants of bank failures in Zimbabwe under the multiple currency environment. The study employed pooled logit estimator using general to specific logit estimation procedure on fourteen banks by making use of the financial panel data for the period 2009-2012. Empirical findings indicated that the macroeconomic environment, in particular GDP growth rate, has much influence on bank failure than any of bank fundamentals. Among bank fundamentals, liquidity, profitability and capitalisation proved to be prominent bank related determinants of bank failures in their respective order. Findings also suggest that loan-to-deposits ratio (LTD), deposits-to-assets ratio (DTA), gross revenue ratio (GRR), return on assets(ROA), efficiency ratio(EFR), SIZE and GDP growth rate (GDP) variables are negatively correlated to the possibility of banks failing while loan-to-assets (LTA) have positive influence on bank failures. Based on these findings the researcher recommends that RBZ must accentuate liquidity and capital requirements since both liquidity and capital ratios were significant and had higher marginal effects. Undoubtedly, the researcher recommends banks to curtail their operating expenses and also improve managerial efficiency so as promote and maintain bank safety and soundness and this will result in remarkable improvements in both profitability and efficiency